Particle breakage characteristics of calcareous sand under confined compression tests - Zhijiang Li; Biwen Zhang; Yani Lu; Xinlian Chen; Yan Wu; Mingxing Luo; Li Zhong (Scientific Reports)
Abstract Calcareous sand is a widely used foundation material in marine engineering. Particle breakage can lead to an increase in its compressibility, affecting the safety and stability of structures. The compression characteristics and particle breakage effects of calcareous sand were analyzed through 33 sets of confined compression tests using calcareous sand specimens. The initial void ratios of the specimens were set between 1.0 and 1.3, and three gradations were selected: 1–2 mm, 0.5–1 mm and 0.25–0.5 mm. Moreover, the loading–unloading–reloading tests were conducted. The initial test was loaded to a maximum of 2 MPa and began to unload to 0.4 MPa and then to load to 6 MPa. The test results indicated that the deformation of calcareous sand during compression was mainly plastic deformation, which was irreversible or irrecoverable. With the increase in the vertical pressure, the compression curves of the specimens under different initial void ratios gradually converged to a common straight line. With the increase in the loading, the existence of particle size less than 0.074 mm in the specimen showed a decreasing trend, and all types of particle breakage indices showed an increasing trend. The particle size of the specimen was larger, the value of the breakage index was larger. Comparison of multiple breakage indices proposed by researchers revealed that the breakage indices increased with the increase in the vertical pressure. Some breakage indices cannot adequately represent the wholeness of the gradation curves and are not easy to be used as breakage index. Generally, the relative breakage index of Hardin B r was smaller than the relative breakage index of Einav B e , and there was a close relationship between the two. The test results can provide theoretical guidance for the construction of calcareous sand islands and reefs.